Effect of Liquid Organic Fertilizer from Lamtoro Leaves, Leri Water, and Coconut Fiber on the Growth of Land Kale (Ipomoea reptans Poir.) - Harimurti, Sabina Azzahra; Ratnasari, Evie (LenteraBio : Berkala Ilmiah Biologi, 2025)
Lamtoro leaves, leri water, and coconut fiber are organic materials and wastes containing macronutrients and micronutrients, thus they can be used as basic ingredients for liquid organic fertilizer (LOF). This research aims to know the nutrient content of LOF and the effect of its administration, as well as the most optimal concentration on the growth of land kale plants. The research was designed using one-factor Randomized Block Design. LOF were applied at five concentrations; P0 = inorganic; P1 = 10%; P2 = 20%; P3 = 30%; P4 = 40%. Plant growth parameters measured were plant height, number and length of leaves, and plant wet biomass. Statistical data analysis used one-way ANOVA test, followed by Duncan test. Results showed that the nutrients of LOF with lamtoro, leri, and coconut fiber were N 0.92%; P 0.01%; K 0.23%; C/N ratio 6.5; Fe 128.65 mg/kg. LOF was found affecting the growth of land kale plants. Among the four LOF concentrations, the most optimal concentration was 40% on all growth parameters. However, plants treated P0 treatment still had higher growth parameters compared to LOF treatments.